Measurement of Road Safety Decade of Action Program Performance in Indonesia - Aprianto, Rizal; Syaban, Alfath Satria Negara (Universitas Islam Sultan Agung Semarang, 2023)
ABSTRACT Even though the government has established the National General Plan for Road Traffic and Transportation Safety (RUNK LLAJ), questions about the effectiveness and performance measurement of this program still remain. Therefore, further research is needed to optimize traffic safety and road transportation in Indonesia. This study aims to determine how to measure the performance of the implementation of Traffic and Road Transportation safety in the National Scope, DKI Jakarta Province, and Sukoharjo Regency based on the criteria/indicators of the five Pillars and their action programs, as well as knowing the use of methods used in measuring the performance of their implementation. This research was conducted by direct observation in the field using a data collection tool in a questionnaire and analyzed using the Analytic Network Process (ANP) and Rating Scale methods. ANP is used to determine the weighting, and the Rating Scale is used to score the performance questionnaire. Based on the results of the analysis that has been carried out, it is known that the performance of the implementation of Traffic and Road Transportation safety in the National Scope is in the